(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Working capital is defined as the sum of money required to meet enterprise’s running expenses The article investigates the quantological approach of working capital management on profitability of Indian companies in the area of cosmetics listed on NSE for 10 years from 2012 to 2021. The independent variable taken for the research are inventory ratio, Debtors ratio, interest coverage ratio, debt equity ratio, Fixed assets turnover ratio and current ratio while profitability is a dependent variable. The study finds that DER and CR is a very important variable from view point of the sustainable profitability of the company and should be given more importance by managers of the company.